2020
DOI: 10.1016/j.ijbiomac.2019.11.043
|View full text |Cite
|
Sign up to set email alerts
|

Improving the catalytic performance of Proteinase K from Parengyodontium album for use in feather degradation

Abstract: Proteinase K (PROK) from Parengyodontium album hydrolyzes keratin, a major protein component of poultry feathers, which are an inexpensive and renewable protein resource. Based on structural studies for analysis of amino acid flexibility near the catalytic center, identification of highly conserved residues, and experimental screening, we obtained a mutant R218S with residual activity 1.6-fold higher than that of PROK after incubation at 60 °C for 1 h. Molecular dynamics simulation indicated that substitution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…As shown in Figure 4, DgeKer and DgeKer-C exhibited maximal activity at 70 • C, which was higher than most of the other keratinases [18,32], such as KerA-derived (50 • C) [30] and MtaKer (65 • C) [11]. In terms of thermostability, DgeKer-C performed better than DgeKer (Figure 4).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As shown in Figure 4, DgeKer and DgeKer-C exhibited maximal activity at 70 • C, which was higher than most of the other keratinases [18,32], such as KerA-derived (50 • C) [30] and MtaKer (65 • C) [11]. In terms of thermostability, DgeKer-C performed better than DgeKer (Figure 4).…”
Section: Discussionmentioning
confidence: 93%
“…Chicken feathers degradation was carried out according to Yaxin Ren [18] with some modifications. Chicken feather was previously washed and cleaned with detergent and tap water, followed by soaking in 70% ethanol for 1 h and drying.…”
Section: Chicken Feather Degradation In Vitromentioning
confidence: 99%
“…This study shows that digestive enzymes of the black carpet beetle exhibit proteolytic and keratinolytic activity that rivals that of a solution of commercial Proteinase K at a working concentration of 1mg/ml which is 5–10 times the normal working concentration for proteolysis (50–250 µg/ml) (Ren et al., 2020). Furthermore, it shows that these enzymes are functional at nearly room temperature conditions, and neutral pH, which makes them ideal for maximizing sustainability during large scale applications.…”
Section: Discussionmentioning
confidence: 95%
“…The preliminary data reported indicated that plant proteases are suitable to be applied in combination with other enzymes (trypsin and proteinase K) to achieve feasible yields in keratin degradation has been reported. [159]…”
Section: Bird Feathers Valorizationmentioning
confidence: 99%